2015
DOI: 10.1007/s10897-015-9914-9
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive‐Compulsive Disorder: The Process of Parental Adaptation and Implications for Genetic Counseling

Abstract: Obsessive-compulsive disorder (OCD) has primarily pediatric onset and well-documented unique impacts on family functioning. Limited research has assessed the understanding that parents of children with OCD have of the etiology of the condition, and there are no data regarding potential applications of genetic counseling for this population. We recruited 13 parents of 13 children diagnosed with OCD from the OCD Registry at British Columbia Children's Hospital, and conducted qualitative semi-structured telephone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Research has shown that members of families affected with psychiatric illnesses such as schizophrenia, bipolar disorder and obsessive-compulsive disorder are in favor of having access to PGC (Andrighetti et al, 2016;DeLisi & Bertisch, 2005;Martorell et al, 2019;Peay et al, 2009). Furthermore, there is evidence that those who have accessed this intervention have gained important benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that members of families affected with psychiatric illnesses such as schizophrenia, bipolar disorder and obsessive-compulsive disorder are in favor of having access to PGC (Andrighetti et al, 2016;DeLisi & Bertisch, 2005;Martorell et al, 2019;Peay et al, 2009). Furthermore, there is evidence that those who have accessed this intervention have gained important benefits.…”
Section: Introductionmentioning
confidence: 99%
“…To test the hypotheses (see purpose section), first, participants were asked to use a visual analog scale to indicate how guilty, ashamed, stigmatized, looked down upon, and differently treated they felt as a result of having an eating disorder. Then, each participant was presented with two vignettes (adapted from Andrighetti et al, 2016; see Box 1) that depicted two different elements of genetic counseling—specifically, counseling around eating disorder etiology (a fundamental component of the genetic counseling encounter, Vignette 1), and counseling around risks for recurrence and risk reduction strategies (an important component of genetic counseling that is provided for specific patients as indicated, Vignette 2). All participants read the vignettes in the same order (an order that reflects the sequence in which these topics would be addressed clinically), and after reading both, were presented a visual analog scale (identical to the one they completed prior to reading the vignettes) and asked to imagine that they had participated in the interaction with a genetic counselor as described in the vignettes, and to move each slider to reflect how they would feel now about having an eating disorder.…”
Section: Methodsmentioning
confidence: 99%
“…Genetic counseling for psychiatric disorders has been shown to have positive outcomes (Austin & Honer, 2008; Hippman et al, 2016; Inglis, Koehn, McGillivray, Stewart, & Austin, 2015; Moldovan, Pintea, & Austin, 2017; Semaka & Austin, 2019) but is still an underutilized service (Hunter, Hippman, Honer, & Austin, 2010; Moldovan et al, 2019). To shed light on potential explanations for this, previous studies have explored interest in genetic counseling among other populations impacted by mental illnesses (Andrighetti et al, 2016; Austin & Honer, 2008; Austin, Smith, & Honer, 2006; DeLisi & Bertisch, 2006; Erickson et al, 2014; Kalb, Vincent, Herzog, & Austin, 2017; Lyus, 2007; Meiser et al, 2008; Meiser, Mitchell, McGirr, Van Herten, & Schofield, 2005; Quaid, Aschen, Smiley, & Nurnberger, 2001; Quinn et al, 2014; Wilhelm et al, 2009), but none have looked specifically at attitudes of individuals with eating disorders.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report suggests a potential role for genetic counseling as part of the psychoeducation process, with positive impacts on parental treatment orientation. [110] Families can be referred to online resources such as the Pediatric International OCD Foundation website at http://kids.iocdf.org.…”
Section: Treatmentmentioning
confidence: 99%